Modern approaches to learning a foreign language - Belitskii K. A., Zakharova A. A. (Relevant problems of modern science and education, 2024)
This article examines modern approaches to learning a foreign language. From the communicative method to the use of modern technologies, the authors describe in detail the main teaching methods that help students learn a new language more effectively. The article discusses the advantages of each approach, and also emphasizes the importance of choosing the appropriate methodology depending on the individual needs and preferences of students.
Keywords: индивидуализация обучения; practice; практика; изучение иностранного языка; online platforms; онлайн-платформы; Learning a foreign language; целостный подход; когнитивный подход; современные подходы; носитель языка; коммуникативный метод; технологический подход; структурно-функциональный подход; modern approaches; communicative method; technological approach; individualization of learning; native speaker; holistic approach; structural and functional approach; cognitive approach